Identification and functional analysis of chaperonin 10, the groES homolog from yeast mitochondria. - Rospert, S (1993)
Chaperonin 60 (cpn60) and chaperonin 10 (cpn10) constitute the chaperonin system in prokaryotes, mitochondria, and chloroplasts. In Escherichia coli, these two chaperonins are also termed groEL and groES. We have used a functional assay to identify the groES homolog cpn10 in yeast mitochondria. When dimeric ribulose-1,5-bisphosphate carboxylase (Rubisco) is denatured and allowed to bind to yeast cpn60, subsequent refolding of Rubisco is strictly dependent upon yeast cpn10. The heterologous combination of cpn60 from E. coli plus yeast cpn10 is also functional. In contrast, yeast cpn60 plus E. coli cpn10 do not support refolding of Rubisco. In the presence of MgATP, yeast cpn60 and yeast cpn10 form a stable complex that can be isolated by gel filtration and that facilitates refolding of denatured Rubisco. Although the potassium-dependent ATPase activity of E. coli cpn60 can be inhibited by cpn10 from either E. coli or yeast, neither of these cpn10s inhibits the ATPase activity of yeast cpn60. Amino acid sequencing of yeast cpn10 reveals substantial similarity to the corresponding cpn10 proteins from rat mitochondria and prokaryotes.